(untitled) (Nexo Revista Científica, 2012)
The design consists of a device, adapted to a horizontal lathe, for the surface plastic deformation using a roller for refurbishing damaged shafts in the core of the product by friction during operation. These are shafts working under conditions of high contamination by dirt and low speeds to endure high loads, in contact with sliding bearings lubricated by splashes. After two or three years of work they have to be withdrawn from operation due to the high deterioration of the stumps, while internally they have no symptoms of fatigue. After applying the surface treatment to the shaft, the for symptoms of deterioration appear during a period of time which is twice, respect the normal one. The device was designed, manufactured and put into operation adapted to the horizontal lathe. The device was implemented in the recuperation of the axels for the cage cars in the railway transportation of sugar cane. It guarantees the quality of the surface finish and the wear resistance, without affecting railway safety requirements. DOI: http://dx.doi.org/10.5377/nexo.v25i1.794 Nexo Revista Científica,Vol. 25, No. 01, pp.22-27/Junio 2012